Apuntes para una revalorización del arte colonial con relación a Dios. El misticismo de Sor Francisca Josefa del Castillo (2020)
Through the 'Spiritual Affections' of the Abbess of Tunja, Sister Francisca Josefa de la Concepción del Castillo, a reflection on colonial art is posed around the question of its apparent usefulness as a 'vehicle of evangelization', investigating its genuine purpose in the mysticism of the Mother of the Castle and the relationship of her work with Him. The aesthetic purpose of the work of colonial art is to bring the Divine closer to the human, trying to reflect and communicate the testimony of a mystical spiritual search and experience lived by the author, inspired and revealed by God.